Prevalence of Root Canal Treated Anteriors in Patients Seeking Orthodontic Treatment - Purva Verma1 , Naveen Kumar.M2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
A definitive relationship exists between a root canal treated teeth and orthodontic tooth movement. Aim ofthis study was to assess the prevalence of root canal treated anteriors in the patients reporting for orthodontictreatment. Orthopantomogram of 550 patients were assessed for presence of any endodontically treatedupper and lower anterior and was re-verified with the clinical data. Descriptive Statistics was used to torepresent the data.Chi- Square test was done to evaluate the association of RC Treated anteriors between thegenders.Prevalence of endodontically treated anterior teeth was found 0.4% was found in the current study.Highest prevalence was of maxillary central incisors ,secondary to trauma , in 96% cases. Maxillary CentralIncisors are expected to be involved in trauma more frequently and therefore have higher incidence of rootcanal treatment. Multi-centre approach is needed before generalising the results to the entire population.